Demand: "Q1 = 15 -3p1 + p2"
Demand: "Q2 = 6 -2p2 + p1"
Supply: "Q1 = 2 + p1"
Supply: "Q2 = 1 + p2"
At equilibrium, demand = supply
"15 -3p1 + p2 = 2 + p1\\\\\n13 = 4p1 - p2 --------> equation(1)"
At equilibrium, demand = supply,
"6 -2p2 + p1 = 1 + p2\\\\\n5= -p1+ 3 p2 --------> equation(2)"
Solving the two equation gives:
"p2 = 4p1 - 13\\\\\n5 = -p1 + 3(4p1 -13)\\\\\n5 = -p1 + 12p1 - 39\\\\\n44 = 11p1\\\\\np1 = 4\\\\ p2 = 4 \\times 4 - 13\\\\\np2 = 3"
Supply, "Q1 = 2 + p1\\\\"
"Q1 = 2 + 4\n\\\\Q1 = 6\\\\\nQ2 = 1 + p2\\\\\nQ2 = 1 + 3 \\\\Q2 = 4"
"p1 = 4,\\ p2 = 3,\\ Q1= 6,\\ Q2 = 4"
Comments
Leave a comment